Efikasi diri dan motivasi: sebagai mediasi pengaruh pendidikan kewirausahaan terhadap minat berwirausaha - Mega Silvia Karen Hapuk; Suwatno Suwatno; Amir Machmud (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
This research is motivated by the low entrepreneurial intentions of Vocational High School (SMK) students in the city of Bandung. This study aims to determine and analyze the mediating effects of self-efficacy and motivation on the effect of entrepreneurship education on students' entrepreneurial intention. The method used in this study is an explanatory survey research with data collection techniques through questionnaires and observation. The population of this study was all students of class XI class 2018/2019 as many as 7,913 students, while based on Slovin calculations the sample of this study was 400 students. The collected data is then analyzed using descriptive analysis techniques and multiple linear regression with Moderate Regression Analysis (MRA). The results showed that: 1) the level of self-efficacy, motivation, entrepreneurship education and entrepreneurial intention of students was in the very high category. 2) entrepreneurship education influences students' entrepreneurial intention. 3) self-efficacy and motivation mediate the effect of entrepreneurship education on students' entrepreneurial intention. These findings indicate that to increase entrepreneurial intention, the learning process in high school needs to be emphasized in efforts to increase self-efficacy and motivation.